High‐Throughput Platform for Novel Reaction Discovery. Issue 50 (21st July 2022) - Lu, Xiao; Luo, Zhiji; Huang, Ruili; Lo, Donald C.; Huang, Wenwei
Abstract: Detecting the formation of new chemical bonds in high‐throughput synthesis is limited by the efficiency and scalability of reaction product detection, as conventional methods for isolating product from reaction mixtures are time consuming and labor intensive. Here, we report a miniaturizable purification method that enables the rapid, high‐throughput isolation of quaternary ammonium‐tagged products from reaction mixtures with excellent purity using inexpensive equipment that easily can be set up in a typical organic chemistry laboratory. This novel purification technique enabled us to establish a high‐throughput reaction discovery platform. We validated this platform in a screen of 1536 reactions, and one previously unreported transformation was identified. Abstract : Extract, isolate and discover : We have designed a simple technique that can rapidly isolate reaction products with excellent purity by solid‐phase extraction. This unique technique enabled us to develop a high‐throughput reaction discovery platform. The effectiveness of this strategy was demonstrated by one newly discovered transformation, which shed light on the laboratory‐scale discovery of new reactions.